A pilot study on the proposed computer-based SDI service for SEAFDEC Aquaculture Department's scientists and researchers using MINISIS query processor - Ortega, Maribeth C. (1986)
The QUERY processor of MINISIS, a relational data base management system, was used in the pilot study on computer-based SDI involving thirteen SEAFDEC researchers and scientists as users. User profiles were constructed using the ASFA (Aquatic Sciences and Fisheries Abstracts) Thesaurus and matched with as in-house data base of 5,400 records taken from the ASFA 1983 edition. Two computer runs were conducted which retrieved 373 records as hits, of which 59.5 percent were judged as relevant by the users. A high precision was therefore obtained involving about half of the profiles in the first run and subsequently the other half in the second run after profile modification.